Studies on the immunogenicity of protamines in humans and experimental animals by means of a micro-complement fixation test. - Samuel, T (1978)
A complement fixation study with human, monkey and rabbit sera, using purified sperm nuclear basic proteins as antigens, led to the following conclusions. (1) Protamines, the sperm-specific basic nuclear proteins, may be immunogenic in mammalians. (2) Antibodies detected in the indirect immunofluorescence test on human swollen sperm heads in sera from infertile and vasectomized men, are directed primarily against human protamines. (3) The results obtained suggested that differences in the immunization site and/or in the configuration of the immunizing protamine, may lead to the formation of antibodies directed against different antigenic determinants. Autoimmunity to protamines, following vasectomy or in infertile men, is accompanied by the formation of antibodies cross-reacting with common antigenic determinants present in protamines of other species. Induction of immunity to protamines by means of immunization with protamines-RNA complexes (in rabbits), or protamine-insulin complexes (in humans), leads to the formation of antibodies reacting more specifically with the immunizing protamine, showing only slight cross-reaction with other protamines. (4) The histone-like fraction present in mature human spermatozoa is composed mainly of histone fraction H2B.